Development of Polypyrrole/Graphene Oxide Gas Sensor for Detection of Coffee Aroma - Muflihah, Yeni Maulidah; Ardyanti, Zona Salsabila; Zein, Inayatul Aulia Rizka; Zulfikar, Zulfikar; Siswoyo, Siswoyo; Asnawati, Asnawati; Mulyono, Tri (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Detecting and characterizing coffee aroma is crucial for determining the quality of coffee. While gas chromatography is the standard method, using gas sensors is a feasible alternative. The electrode material used extensively influences the response produced by the gas sensor. This study explores using composites of the conductive polymer polypyrrole (PPy) and graphene oxide (GO) as materials for gas sensor electrodes. In the study, we synthesized PPy and GO and characterized them using UV-Vis and FTIR spectrophotometry, confirming that the compounds obtained were PPy and GO. The researchers varied the composition and thickness of PPy/GO in electrode fabrication. Varying the percentage of GO in the composite by 0, 5, 10, and 15% GO resulted in different PPy/GO compositions, while electrode thicknesses observed were 0.083, 0.21, 0.39, and 60 mm. Electrode characterization, including sensitivity, conductivity, and response time, showed that the PPy/GO electrode with a composition of 15% GO and a thickness of 0.21 mm had the best response. The PPy/GO sensor was tested on the aroma of Robusta coffee from three different plantations in the Jember area, East Java. It was able to distinguish the aroma of coffee. Measurement of electrode reproducibility in measuring each sample for one month showed consistent results from week to week, with a %RSD of less than 5%. The research results demonstrate that the PPy/GO sensor with a GO composition of 15% and a thickness of 0.21 mm has excellent potential for differentiating the aroma of coffee with different compositions of constituent compounds.